ADHD and Comorbid Coordination Disorder - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The cooccurrence of attention deficits and motor incoordination or clumsiness was examined at the University of Goteborg in a population study of 400 seven-year-old children attending mainstream schools in Karlstad, Sweden.